1995
DOI: 10.1021/np50126a016
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites of Daidzein and Genistein and Their Biological Activities

Abstract: A number of metabolites of daidzein and genestein have been synthesized and their biological activities determined. Equol [3], 5,7,4'-trihydroxyisoflavan [5], 4,7,4'-trihydroxyisoflavan [6], dihydrodaidzein [8], and dihydrogenistein [9] were synthesized either from daidzein [1] or genistein [2] by hydrogenation. Similarly, the derivatives 4, 7, and 11 were synthesized from 3, 6, and 10, respectively. During acetylation and nmr experiments, 9 was converted to a novel enol intermediate [10]. Antifungal, antibact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 16 publications
2
56
0
1
Order By: Relevance
“…strain Niu-O16 (52), the C-ring cleavage yielding 6Ј-hydroxy-O-desmethylangolensin and subsequently 2-(4-hydroxyphenyl)propionic acid is catalyzed by Eubacterium ramulus (39,51). Although proposed to be a metabolite of microbial genistein conversion (2,11), so far, 5-hydroxy-equol has been detected neither in vitro nor in vivo as a product of the human or rat intestinal microbiota. This suggests that strain Mt1B8 is not common in humans and rats but is specific to mice.…”
Section: Resultsmentioning
confidence: 99%
“…strain Niu-O16 (52), the C-ring cleavage yielding 6Ј-hydroxy-O-desmethylangolensin and subsequently 2-(4-hydroxyphenyl)propionic acid is catalyzed by Eubacterium ramulus (39,51). Although proposed to be a metabolite of microbial genistein conversion (2,11), so far, 5-hydroxy-equol has been detected neither in vitro nor in vivo as a product of the human or rat intestinal microbiota. This suggests that strain Mt1B8 is not common in humans and rats but is specific to mice.…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis may be sup-ported by some previous findings. Namely, genistein was found to act as an inhibitor of DNA topoisomerases type I (Chang et al 1995) and type II (Azuma et al 1995;Chang et al 1995;Constantinou et al 1995;Yamagishi et al 2001;Snyder & Gillies 2002;Verdrengh et al 2004). It was revealed that daidzein possesses the inhibitory activity against topoisomerase I and weakly inhibits topoisomerase II (Chang et al 1995;Sun et al 1998;Yamagishi et al 2001), while kaempferol undoubtedly inhibits topoisomerase II (Constantinou et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Many ASR-regulated CYPs also are classified with electron transport functions (GO:0006118) and, thus, their involvement in the phenylpropanoid pathway also may cause the overrepresentation of electron transport functions. The phenylpropanoid pathway is involved in the biosynthesis of phytoalexins and antimicrobial compounds, including diadzein, genistein, glyceollin, tannins, and cell-wall-reinforcing compounds such as lignans and lignins (Abbasi et al 2001;Chang et al 1995;Chiang and Norris 1983;Hahlbrock and Scheel 1989). In both resistant and susceptible plants, mRNAs encoding these enzymes were induced during the early, general defense response against ASR infection, but most genes returned to mock levels by 24 hai.…”
Section: Potential Biological Roles Of Asr-regulated Genesmentioning
confidence: 99%